2017
DOI: 10.1371/journal.pbio.1002598
|View full text |Cite
|
Sign up to set email alerts
|

Neurocomputational mechanisms underlying subjective valuation of effort costs

Abstract: In everyday life, we have to decide whether it is worth exerting effort to obtain rewards. Effort can be experienced in different domains, with some tasks requiring significant cognitive demand and others being more physically effortful. The motivation to exert effort for reward is highly subjective and varies considerably across the different domains of behaviour. However, very little is known about the computational or neural basis of how different effort costs are subjectively weighed against rewards. Is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
448
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(534 citation statements)
references
References 81 publications
34
448
2
Order By: Relevance
“…For most participants, modafinil appeared to facilitate endurance performance. Mechanistically, this could be through altering the neuromodulatory environment related to effort and motivationally based behaviour (e.g., see Minzenberg & Carter, 2008), consistent with enhancing cognitive control processes (e.g., see Chong et al, 2017;Esposito et al, 2013) as has been previously proposed (Battleday & Brem, 2015). However, overall, we did not find significant results.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…For most participants, modafinil appeared to facilitate endurance performance. Mechanistically, this could be through altering the neuromodulatory environment related to effort and motivationally based behaviour (e.g., see Minzenberg & Carter, 2008), consistent with enhancing cognitive control processes (e.g., see Chong et al, 2017;Esposito et al, 2013) as has been previously proposed (Battleday & Brem, 2015). However, overall, we did not find significant results.…”
Section: Discussionsupporting
confidence: 67%
“…Modafinil may improve performance normally inhibited with mental fatigue thorough enhancement of cognitive control processes (see Battleday & Brem, 2015). Modafinil alters activation of front-parietal control and dorsal attentional networks (Cera, Tartaro, & Sensi, 2014;Esposito et al, 2013) implicated in the cognitive processes that coordinate the pursuit of a goal (e.g., Chong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another indication that effort is costly comes from the finding that people are often willing to accept fewer rewards to avoid effort [61,62]. That is, just as people discount rewards by their associated delays [63,64], so too do they discount rewards by the amount of cognitive or physical effort required to obtain them (i.e., effort discounting ) [21,65]. …”
Section: Effort Is Costlymentioning
confidence: 99%
“…Of course, decision-making is linked to cognitive processes, but in a recent study, Verdejo-Garcia et al [6] showed that decisions could be impaired with preserved executive functions. To make a choice between different options, the value of each option is examined, subserved by different areas [8]. Compared to controls, alcoholics had widespread reduced gray matter volume in the ventromedial prefrontal cortex, dorsal anterior cingulate and right hippocampal formation [9,10].…”
Section: Introductionmentioning
confidence: 99%